Reproductive Factors, Exogenous Hormone Use, and Risk of B-Cell Non-Hodgkin Lymphoma in a Cohort of Women From the European Prospective Investigation Into Cancer and Nutrition. Issue 2 (27th November 2018) - Costas, Laura; Lujan-Barroso, Leila; Benavente, Yolanda; Allen, Naomi E; Amiano, Pilar; Ardanaz, Eva; Besson, Caroline; Boeing, Heiner; Bueno-de-Mesquita, Bas; Cervenka, Iris; Fortner, Renée T; Fournier, Agnès; et al.
Abstract: The role of hormonal factors in the etiology of lymphoid neoplasms remains unclear. Previous studies have yielded conflicting results, have lacked sufficient statistical power to assess many lymphoma subtypes, or have lacked detailed information on relevant exposures. Within the European Prospective Investigation Into Cancer and Nutrition cohort, we analyzed comprehensive data on reproductive factors and exogenous hormone use collected at baseline (1992–2000) among 343, 458 women, including data on 1, 427 incident cases of B-cell non-Hodgkin lymphoma (NHL) and its major subtypes identified after a mean follow-up period of 14 years (through 2015). We estimated hazard ratios and 95% confidence intervals using multivariable proportional hazards modeling. Overall, we observed no statistically significant associations between parity, age at first birth, breastfeeding, oral contraceptive use, or ever use of postmenopausal hormone therapy and risk of B-cell NHL or its subtypes. Women who had undergone surgical menopause had a 51% higher risk of B-cell NHL (based on 67 cases) than women with natural menopause (hazard ratio = 1.51, 95% confidence interval: 1.17, 1.94). Given that this result may have been due to chance, our results provide little support for the hypothesis that sex hormones play a role in lymphomagenesis.